Durability characterization of landslide material from mudrock of Jatiluhur formation - Misbahudin Misbahudin; Ismail Suny Pardede (Brawijaya University, 2023)
The infrastructure project has many lies on the mudrock foundation. Some reports in Hambalang, West Java, Indonesia, state the engineering problem related to landslides and foundation failure due to mudrock material's existence. The mudrock originated from Jatiluhur Formation. The problem is also present in slope stability, such as surface erosion and landslide on the many slopes. Landslide material from mudrock material has easily broken into smaller fragments. This research used the wet-dry cycle to evaluate mudrock's durability to weathering on a laboratory scale. The preparation of the test samples in the form of intact rock with a weight of 450-550 grams and then open exposure under sun dry was conducted. The sample was then immersed in water for 24 hours. ISRM physical properties were conducted and correlated with statistical analyses to determine factors affecting the mudrock's durability. From the index of durability, mudrock in Jatiluhur Formation in this research area had various degrees of disintegration. The siltstone samples remained intact until the 15th cycle, unlike shale and claystone samples had expressed low durability and rapid disintegration rate. A series of investigation durability characteristics of mudrock in this study can be applied to other samples and formations that are quantitively and qualitatively.